The transforming influence of the Greeks on Roman medical practice - Cilliers, Louise; Retief, Francois (University of the Free State, 2007)
When Rome conquered Greece in the second century BC, she had no equivalent to Greek rational medicine as established by Hippocrates and the Alexandrians. Roman medicine was of a quasi-religious nature, with a strong element of folk traditions and herbal medicine; the paterfamilias would treat any sickness in the family (including slaves and even animals) with his array of folk remedies. Greek rational medicine was initially received with great skepticism by the Roman elite, in particular, but it gradually transformed the scene, replacing superstition and magic with a reliance on rational science as it was understood at the time. However, the belief in herbal remedies and the Asclepian cult of temple medicine remained strong. Rome also made its own unique contributions in the fields of hygiene (effective water supplies, sewage and drainage) and military medicine (including the introduction of the first hospitals). Roman doctors gradually replaced their Greek colleagues, and by the fifth century Latin had established itself as a significant medical language. In practice Roman folk medicine was not necessarily much inferior to Greek rational medicine, because the latter was based on ill-understood and largely erroneous concepts of medical science.

Toe Rome Griekeland in die tweede eeu vC verower, was daar geen Romeinse ekwivalent van Griekse rasionele geneeskunde soos daargestel deur Hippokrates en die Aleksandryne nie. Romeinse geneeskunde was van kwasi-religieuse aard, deurdrenk met volkstradisies en kruie-medikamente; die paterfamilias het binne familieverband siekes (familielede, slawe, selfs diere) met ’n verskeidenheid volksgeneesmiddels behandel. Griekse rasionele geneeskunde, aanvanklik deur veral die Romeinse elite baie skepties ontvang, het egter stelselmatig die Romeinse toneel getransformeer. Die impak van bygeloof en magiese kragte is verplaas deur vertroue in die natuurwetenskap soos destyds verstaan. Kruiegeneeskunde en die Asklepios-kultus se tempel-geneeskunde het egter invloedryk gebly, en Rome het ook ’n eie unieke bydrae gelewer in die veld van higiëne (veral deur voorsiening van water, dreinering en riolering) en militêre geneeskunde (daarstelling van die eerste hospitale). Griekse geneeshere is mettertyd deur Romeinse kollegas vervang, en teen die die vyfde eeu het Latyn ’n beduidende mediese skryftaal geword. Weens ’n grotendeel foutiewe begrip van basiese mediese wetenskappe was Griekse rasionele geneeskunde in die praktyk nie noodwendig meer effektief as Romeinse volksgeneeskunde nie.
Keywords: Roman medicine; Folk remedies; Greek rational medicine; Hippocratic Corpus; Medical practice